Long-Term Economic Implications of Demeny Voting: A Theoretical Analysis - Luigi Bonatti; Lorenza Alexandra Lorenzetti (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper places itself at the intersection between the literature on "Demeny voting" (the proposal of letting custodial parents exercise their children's voting rights until they come of age) and the vast literature on formal models with endogenous fertility that address the problem of fiscal redistribution between young and old cohorts in the presence of an aging population. Linking these issues to the process of economic growth through a simple overlapping generations model, we show that, even if the government is myopic, in the sense that it cares only about the current well being of the living (and voting) generations, an increase in the relative importance that it attaches to the interests of the young cohort (for instance, due the introduction of Demeny voting) leads in the long run to a higher population growth rate and raises the consumption level of each young adult, the capital stock per worker and the output per adult. We also show that in the long run such a reform raises the well being that individuals can expect at birth to achieve during their lifetime.
Keywords: D10; D72; H23; J13; O41; 330; OLG model; fertility; fiscal redistribution; well being; child allowances